Кислотно-основные и адсорбционные свойства поверхности металлокерамических композитов на основе нитрида кремния - Казанцева, Ксения Игоревна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
Silicon nitride-based composites are advanced photocatalysts for oxidative pharmaceutical wastewater treatment. In the present study, the acid-base properties of the composite materials were investigated by the Hammett and Tanabe indicator method. The diversity of acid-base centers on the surfaces of the composites was established. Also, the correlation of the adsorption activity to chloramphenicol with the nature and number of active centers was shown.